Avaliação algimétrica por estímulo nociceptivo térmico e pressórico em cães pré-tratados com levomepromazina, midazolam e quetamina associados ou não ao butorfanol ou buprenorfina - Rosa, André Leguthe; Massone, Flávio [UNESP] (Sociedade Brasileira para o Desenvolvimento da Pesquisa em Cirurgia, 2005)
This study aimed at quantifies the pain in dogs under dissociative anesthesia, across thermal and pressoric stimulus and quantify the reasonable period between two different opioids analgesics. In this study, 30 dogs were used and, divided into three groups of 10 animals each, in which the animals of GI received methotrimeprazine and midazolam put on the same syringe with ketamine. The animals of GII received the same treatment of GI but associated with butorphanol and finally the animals of GIII received the same treatment of GI but associated with buprenorphine. The routine parametric evaluations has been proceeded, although using the thermo algimetry measured in degrees C with the average of 52 degrees C and the pressoric algimetry in Kg. In the thermo algimetry, there has been significant difference in GI at the moments M0, M1, M4 and M5; in GII it was found at M0, M1, M5 and M6 and in GIII it was observed the significant at M0 and M1. It has also been shown in pressoric algimetry significant difference in GI at the moments M0, M2 and M3. Among GII it has observed significant difference at all moments and it has found at M0, M9 in GIII. Thus, it has observed significant differences between all groups; for such the M2 of GII smaller than the others; and M4, M5 of GIII bigger than GI and GII. In the assessment of all periods it was observed significant latent period bigger in GI, however, with reasonable period and short recovery in GII and GIII. In the order hand, the postural tonus recovery it was longer in GIII, followed by GII and finally GI. The used method for the measurement of algic stimulus was efficient, noticing a reasonable analgesic period of 3 hours for butorphanol and 6 hours for buprenorphine.

Quantificar a dor em cães sob anestesia dissociativa através de estímulo térmico e pressórico e o período hábil de dois analgésicos opióides. MÉTODOS: Empregaram-se 30 cães alocados em três grupos (n=10), onde os animais de GI receberam levomepromazina e midazolam associado na mesma seringa à quetamina. Os animais de GII receberam o mesmo tratamento de GI porém associado ao butorfanol e por fim os animais de GIII receberam o mesmo tratamento de GI associando-se a buprenorfina. Procedeu se a avaliação paramétrica rotineira, empregando-se, entretanto, a termoalgimetria mensurada em °C em média de 52°C e a pressoalgimetria em kg. RESULTADOS: Na termoalgimetria houve diferença significativa em GI nos momentos M0 e M1,e em M4 e M5. Em GII houve diferença em M0, M1, M5 e M6. Em GIII houve diferença entre momentos M0 e M1. Na pressoalgimetria houveram diferenças em GI em diferentes momentos: M0, M2 e M3. Em GII observaram-se diferenças em todos os momentos. Em GIII observaram-se diferenças em M0 e M9. Ocorreram diferenças entre os grupos, sendo o M2 de GII menor que GI e GIII. Já em M4 e M5 de GIII demonstrou-se maior que GI e GII. E na avaliação dos períodos observou-se um período de latência significativamente maior em GI, porém com período hábil e de recuperação menor em relação à GII e GIII. Já a recuperação do tônus postural foi maior em GIII seguido de GII e finalmente de GI. CONCLUSÃO: O método empregado para mensuração do estímulo álgico foi eficiente, observando-se um período hábil analgésico de 3 horas para o butorfanol e de 6 horas para a buprenorfina.
The algimetry evaluation for thermic and pressoric nociceptive stimulus in pre treated dogs with methotrimeprazine, midazolam and ketamine associated or not with butorphanol or buprenorphine
Keywords: Analgesia; Algimetry; Dissociative Anesthesia; Butorphanol; Buprenorfine; Dog; Analgesia; Algimetria; Anestesia dissociativa; Butorfanol; Buprenorfina; Cão